2015
DOI: 10.14687/ijhs.v12i1.3068
|View full text |Cite
|
Sign up to set email alerts
|

The development of Irrational Romantic Relationship Beliefs Inventory<p>Romantik İlişkilerde Akılcı Olmayan İnançlar Ölçeği’nin geliştirilmesi

Abstract: In this study, the Irrational Romantic Relationship Beliefs Scale (RAINO) was developed and the validity and reliability of the scale were investigated. The scale was developed based on the theories of Ellis (1986) and Beck (2011), for the purpose of evaluating the irrational relationship beliefs of the individuals. In the beginning the number of items were 98, and after the factor analysis it became a 30 item-ed, 5 likert tpye scale. The participants in this study consisted 551 university students, whose resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…Irrational Relationship Beliefs Inventory (IRBI): For the psychometric properties of IRBI, developed by Sarı and Korkut Owen (2015), exploratory and confirmatory factor analysis, criterion validity and internal consistency coefficient were used. The exploratory variance showed that the scale had six factors, Over Expectations (OE), Use of Social Time (UST), Mind Reading (MR), Different Thinking (DT), Physical Intimacy (PI) and Gender Differences (GD).…”
Section: Data Collection Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrational Relationship Beliefs Inventory (IRBI): For the psychometric properties of IRBI, developed by Sarı and Korkut Owen (2015), exploratory and confirmatory factor analysis, criterion validity and internal consistency coefficient were used. The exploratory variance showed that the scale had six factors, Over Expectations (OE), Use of Social Time (UST), Mind Reading (MR), Different Thinking (DT), Physical Intimacy (PI) and Gender Differences (GD).…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…Physical Intimacy sub-dimension is on the unrealistic statements about physical intimacy. Gender Differences sub-dimension is a dimension where unrealistic statements are put forth about the effect of gender differences on the relationship (Sarı & Korkut Owen, 2015).…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…Düşünceleri belirlemeye yönelik olarak geliştirilen ölçme araçlarına bakıldığında özellikle sorun ya da duruma özgü olarak geliştirildiği de görülmektedir. Örneğin; Kaya (2018) tarafından Akademik Başarıya İlişkin Bilişsel Çarpıtmalar Ölçeği'nin, Sarı ve Owen (2015) tarafından Romantik İlişkilerde Akılcı Olmayan İnançlar Ölçeği'nin, Sprecher ve Metts, (1989) tarafından geliştirilen ve Türkçe uyarlaması Küçükarslan ve Gizir (2013) tarafından yapılan Romantik İnançlar Ölçeği, Hamamcı ve Büyüköztürk (2003) tarafından geliştirilen İlişkilerle İlgili Bilişsel Çarpıtmalar Ölçeği, Hill ve Safran (1994) tarafından geliştirilen ve Boyacıoğlu ve Savaşır (1995) tarafından Türkçe Uyarlaması da yapılan Kişilerarası Şema Ölçeği, Gündüz (2006) tarafından geliştirilen Akılcı Olmayan İnançlar Ölçeği Öğretmen Formu, Erdem ve Bilge (2008) tarafından geliştirilen Lise öğrencileri için Meslek Seçimine İlişkin Akılcı Olmayan İnançlar Ölçeği, Yeşiltepe-Kaynak (2019) tarafından geliştirilen Lise Seçimine İlişkin Akılcı Olmayan İnançlar Ölçeği, Tülü ve Erden (2014) tarafından geliştirilen Tecavüz Suçuna Yönelik Bilişsel Çarpıtmalar Soru Formu, Kaya ve Hamamcı (2011) tarafından geliştirilen Anne-Babaların Akılcı Olmayan İnançları ölçeği ve Schulman vd. (1986) tarafından geliştirilen Bulimia ile ilişkili Bilişsel Çarpıtmalar Ölçeği gibi ölçme araçlarının olduğu da görülmektedir.…”
Section: Introductionunclassified
“…When the literature is examined that there are measurement tools such as; The Cognitive Distortions Related to Academic Achievement Scale by Kaya (2018) and Irrational Romantic Relationship Beliefs Inventory by Sarı and Owen (2015) were developed by Sprecher and Metts, (1989) and the Turkish adaptation was made by Küçükarslan and Gizir (2013). Romantic Beliefs Scale, Interpersonal Cognitive Distortions Scale developed by Hamamcı and Büyüköztürk (2003), Interpersonal Schema Questionnaire developed by Hill and Safran (1994 and adapted into Turkish by Boyacıoğlu and Savaşır (1995), Irrational Beliefs Scale-Teacher Form by Gündüz (2006), Scale for Irrational Beliefs in Career Choicesof High School Students developed by Erdem and Bilge (2008), Irrational Beliefs Scale for High School Choice developed by Yeşiltepe-Kaynak (2019), Cognitive Distortions Question Tools About Rape developed by Tülü and Erden (2014,) Parent Irrational Belief Scale devoloped by Kaya and Hamamcı (2011) and The Bulimia Cognitive Distortions Scale developed by Schulman et al (1986).…”
Section: Introductionmentioning
confidence: 99%
“…Bilişsel Terapi ve Akılcı Duygusal Davranışçı Terapi çerçevesinde düşünceleri ölçmeye yönelik birçok ölçme aracı geliştirilmiştir. Ancak, Fonksiyonel olmayan tutumlar ölçeği (Savaşır ve Şahin, 1997), Otomatik düşünceler ölçeği (Aydın ve Aydın, 1990) İlişkilerle ilgili bilişsel çarpıtmalar ölçeği (Hamamcı ve Büyüköztürk, 2003) Akılcı olmayan inançlar ölçeği (Türküm, 2016), Anne babaları akılcı olmayan inançları ölçeği (Kaya ve Hamamcı, 2011) Meslek seçimine ilişkin akılcı olmayan inançlar ölçeği (Erdem ve Bilge, 2008) Romantik ilişkilerde akılcı olmayan inançlar ölçeği (Sarı ve Korkut Owen, 2015) gibi bilişsel çarpıtmalar veya akılcı olmayan inançları ölçmeye yönelik geliştirilmiş birçok ölçme aracına olmasına rağmen doğrudan ergenlerin akademik başarıya ilişkin bilişsel çarpıtmalarını ölçmeye yönelik herhangi bir ölçme aracına rastlanmamıştır. İncelenen ölçekler içerisinde Özdel ve diğerleri, (2014) tarafından kişiler arası ilişkiler ve kişisel başarıya ilişkin bilişsel çarpıtmaları ölçmeye yönelik geliştirilen ölçme aracının kişisel başarı alt boyutu, başarıya ilişkin bilişsel çarpıtmaları ölçüyor olmakla beraber genel tanımlamalar (iş veya okul yaşamı gibi) içerdiği, doğrudan akademik başarıya odaklanmadığı ve ölçek yetişkin popülasyona yönelik geliştirildiğinden, ergenler üzerinde doğrudan akademik başarıya ilişkin bilişsel çarpıtmaları ölçecek bir ölçme aracına gereksinim olduğu kanaatine varılmıştır.…”
unclassified